ANALYSIS THE INFLUENCE OF DOCUMENT SERVICE QUALITY, FACILITY, AND THE USE OF ACCEPTANCE ONLINE MODULE TECHNOLOGY TOWARD SERVICE USER SATISFACTION (CASE STUDY AT KPPBC TMP-A SEMARANG) - Tamara Adriana Kusuma; Noor Suroija; Sandi Supaya (Politeknik Negeri Semarang, 2018)
This research aims to analyze the influence of document service quality, facility, and the use of acceptance online module technology toward service user satisfaction (case study at KPPBC TMP-A Semarang). The technique of analysis used in this research was multiple linier regression analysis. The population was the customer who ever used service at KPPBC TMP-A Semarang. Census sampling had been applied as the sample technique and the sample are 48 respondents. The results of t-test showed that document service quality, facility, and the use of acceptance online module technology partially got positive significant influence toward service user satisfaction at KPPBC TMP-A Semarang. Based on the result of F-test document service quality, facility, and the use of acceptance online module technology simultaneously got significant influence toward service user satisfaction at KPPBC TMP-A Semarang. Based on the adjusted R2, 75.1% influence in the service user satisfaction at KPPBC TMP-A Semarang could be explained by document service quality, facility, and the use of acceptance online module technology, while the rest of 24.9% was explained by the other variables outside the model.